1995
DOI: 10.1080/09687599550023723
|View full text |Cite
|
Sign up to set email alerts
|

Disability in an Eastern Religious Context: historical perspectives

Abstract: Disability in the past of eastern religions has attracted little formal or comparative scrutiny. A range is sketched here of historical data, viewpoints and attitudes on disability in Hinduism, Buddhism and Islam, which continue to influence the thoughts of half the world's population. Approaches for more detailed studies are suggested, moving towards such global measures for understanding, remediating and accommodating disability as would be more appropriate and acceptable to the non-western majority. Popular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 0 publications
0
39
0
1
Order By: Relevance
“…149,150 However, although a qualitative study exploring dimensions of QOL for adults with SCI in China identified two unique issues -world peace and harmonious relationships with neighboursmany themes reflected those identified in this synthesis, such as the role of the political, social, economic and physical environment, self-concept, the ability to contribute to others, family relationships and participation in social activities. 58 Using accepted methods 24,25,28,[38][39][40] this study has demonstrated the utility of the meta-synthesis in drawing together the findings of a number of published studies.…”
Section: Discussionmentioning
confidence: 88%
“…149,150 However, although a qualitative study exploring dimensions of QOL for adults with SCI in China identified two unique issues -world peace and harmonious relationships with neighboursmany themes reflected those identified in this synthesis, such as the role of the political, social, economic and physical environment, self-concept, the ability to contribute to others, family relationships and participation in social activities. 58 Using accepted methods 24,25,28,[38][39][40] this study has demonstrated the utility of the meta-synthesis in drawing together the findings of a number of published studies.…”
Section: Discussionmentioning
confidence: 88%
“…Social models, by contrast, argue that societal contexts render such impairments disabling [33]. Moral constructions of disability have a long history in India, with impairments understood as ‘retribution’ for previous ‘deceit, mischief and evil’, rendering the impaired person ‘less capable’ [14,34]. Impairment is frequently constructed negatively in India, and there has been a strong preference for rehabilitative or medical interventions to ‘correct’ impairment, with little attention paid to the disabling impact of the social context [14].…”
Section: Disability In the Indian Contextmentioning
confidence: 99%
“…The main reason is that disability is often seen as the effect of a personal or parental sin in a previous life (Miles, 2002;Singh, Sinha, Banerjee, & Jaswal, 2013). In addition, Pulla (2014a) describes Karma in spiritually sensitive social work practice as not only "the universal causal law" but also "the ethical dimensions of life processes itself or the satvik karma or karma without an attachment to the action" (p. 186).…”
Section: Study Site and Religionmentioning
confidence: 99%